2005
DOI: 10.1002/qua.20769
|View full text |Cite
|
Sign up to set email alerts
|

Table‐CI with macroconfiguration approach for describing electronic states of molecules in intense radiation fields

Abstract: ABSTRACT:Modifications to the recently introduced table-driven multireference configuration interaction (CI) approach that uses macroconfigurations necessary for the efficient construction of electronic Floquet states are described. Adiabatic electronic Floquet states have recently shown promise as simplifying the description of the electronic structure of molecules in intense radiation fields. The algorithm for the tabledriven multireference CI approach that uses macroconfigurations for the calculation of ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…The iterative non-Hermitian Floquet methods can also be used in conjunction with the ab initio electronic structure methods, which have been conventionally used for computing the Field-Free eigen solutions and properties, for solving the photoionization resonances. Interestingly, an ab initio multireference configuration interaction method for the Hermitian Floquet problem has been recently discussed in the literature [25,26,27]. The iterative procedure can also be used for improving the computational efficiency of such a Floquet formalism.…”
Section: Discussionmentioning
confidence: 99%
“…The iterative non-Hermitian Floquet methods can also be used in conjunction with the ab initio electronic structure methods, which have been conventionally used for computing the Field-Free eigen solutions and properties, for solving the photoionization resonances. Interestingly, an ab initio multireference configuration interaction method for the Hermitian Floquet problem has been recently discussed in the literature [25,26,27]. The iterative procedure can also be used for improving the computational efficiency of such a Floquet formalism.…”
Section: Discussionmentioning
confidence: 99%
“…It has recently been shown that the task of calculating electronic Floquet states is amenable to high accuracy methods in modern quantum chemistry, and a variant of the multireference configuration interaction method with single and double excitations ͑MRCISD͒ from a set of reference configurations was introduced for its solution. 6,7 The developed MRCISD-based description of Floquet states was successfully demonstrated on studying the behavior of the lowest six doublet electronic states of Li 2 + in an intense ͑0.9 ϫ 10 12 W/cm 2 ͒ field. 6 In the present work, using the same method, we study the Floquet states of N 2 2+ created by the interactions of the six lowest singlet ͑1 1 ⌺ g + , 1 1 ⌬ g , 2 1 ⌺ g + , 1 1 ⌸ u , 1 1 ⌸ g , and 1 1 ⌺ u − ͒ states of the dication, which correlate with its lowest dissociation asymptote 2N + ͑ 3 P g ͒, in an intense ͑0.4ϫ 10 13 W/cm 2 ͒ radiation field.…”
Section: Introductionmentioning
confidence: 99%